Participation as Promoter and Guardian of Democracy and Citizenship - Mercedes Oraisón (Universidad Autónoma de Madrid, 2016)
This article focuses on the identification and the analysis of conditions and rationalities that conform a participation oriented to emancipation and active citizenship. Fort that, in a first moment, the ideas of two Latin-American thinkers are recovered. In those thoughts, participation is related to a political and democratizing project and to the construction of a critical subjectivity. The effects of that practices are discussed in order to understand the different perspectives and positioning configured there. Finally, we recovered some theoretical conceptions and formal proposal that enable us to think in the factual and normative sceneries where participation looms as promoter and guardian of democracy and citizenship.